Leishmanicidal and Cholinesterase Inhibiting Activities of Phenolic Compounds from Allanblackia monticola and Symphonia globulifera - Norbert Sewald (Molecules, 2007)
In a preliminary antiprotozoal screening of several Clusiaceae species, the methanolic extracts of Allanblackia monticola and Symphonia globulifera showed high in vitro leishmanicidal activity. Further bioguided phytochemical investigation led to the isolation of four benzophenones: guttiferone A (1), garcinol (2), cambogin (3) and guttiferone F (4), along with three xanthones: allanxanthone A (5), xanthone V1 (6) and globulixanthone C (7) as active constituents. Compounds 1 and 6 were isolated from S. globulifera leaves, while compounds 2-5 were obtained from A. monticola fruits. Guttiferone A (1) and F (4) showed particulary strong leishmanicidal activity in vitro, with IC50 values (0.2 Î¼M and 0.16 Î¼M, respectively) comparable to that of the reference compound, miltefosine (0.46 Î¼M). Although the leishmanicidal activity is promising, the cytotoxicity profile of these compounds prevent at this state further in vivo biological evaluation. In addition, all the isolated compounds were tested in vitro for their anticholinesterase properties. The four benzophenones showed potent anticholinesterase properties towards acetylcholinesterase (AChE) and butylcholinesterase (AChE). For AChE, the IC50 value (0.66 Î¼M) of garcinol (2) was almost equal to that of the reference compound galanthamine (0.50 Î¼M). Furthermore, guttiferone A (1) and guttiferone F (4) (IC50 = 2.77 and 3.50 Î¼M, respectively) were more active than galanthamine (IC50 = 8.5) against BChE.